1976
DOI: 10.1071/bt9760641
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Redistribution as Affected by Throughfall and Stemflow in an Arid Zone Shrub Community

Abstract: Changes in soil moisture under various densities of mulga (Acacia aneura F. Muell.) were followed from December 1971 to October 1973. Stemflow was instrumental in storing water at depth in the soil, being particularly noticeable with medium falls of rain (~ 75 mm); heavy (~ 160 mm) falls tended to mask the effect. Throughfall increased linearly with aggregate rainfall, and percentage throughfall decreased with increasing tree density. Of incoming precipitation, 94% was partitioned as throughfall under a tree d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
74
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 5 publications
9
74
2
Order By: Relevance
“…Annual plants were the opportunists in the sand-binding dunes. They only germinated during the rainy season and quickly completed their life cycles [14,27,100,101].…”
Section: Morphological Adjustment and The Regulation Threshold Of Vegmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual plants were the opportunists in the sand-binding dunes. They only germinated during the rainy season and quickly completed their life cycles [14,27,100,101].…”
Section: Morphological Adjustment and The Regulation Threshold Of Vegmentioning
confidence: 99%
“…The interception losses by A. ordosica and C. korshinskii accounted for 15% and 27% of the precipitation on a crown area basis and 6% and 11% of the precipitation on a ground area basis [12,13]. The interception losses were less than those in the Chihuahua and Negev deserts, where the interception loss accounted for 10%-60% of the rainfall [14][15][16][17][18], mainly due to the sparse shrub canopy structure and lower leaf area index. Therefore, with regards to rainfall interception, species with relatively sparse stems and branches should be selected as potential sand-binding species [12,13].…”
Section: Rainfall Interception and Redistribution By Sandbinding Shrubsmentioning
confidence: 99%
“…Previous studies have shown that stemflow can be a major source of tree-induced infiltration and subsequent flow in and below the soil root zone, including recharge (Aboal et al, 1999;Gomez et al, 2002;Liang et al, 2007Liang et al, , 2011Pressland, 1976;Sansoulet et al, 2008;Tanaka et al, 1996). Liang et al (2007) observed that cumulative stemflow per unit infiltration area along the downslope side of a tree trunk was nearly 20 times cumulative open-area rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Návar and Bryan (1990) calculated that stemflow input to the soil area around three semiarid shrub stems in northeastern Mexico represented a water input that was five times higher than by other areas below the shrub canopies. Other arid shrubs are also adapted to divert rainfall to the base of their stems as stemflow where it subsequently infiltrates the soil and remains available for plant uptake at deeper soil layers (Pressland, 1976;Nulsen et al, 1986;Návar, 1993;Martinez-Meza and Whitford, 1996;Li et al, 2008). Levia and Frost (2003) provided a thorough review of the quantitative and qualitative importance of stemflow in forests as well as in agricultural environments.…”
Section: Introductionmentioning
confidence: 99%